Qualitative and Quantitative Analysis of Resveratrol and Oxyresveratrol by Liquid Chromatography - Khambadkar, Rajeshree; Ravindran, Selvan; Chahar, Digamber S.; Utekar, Srushti; Tambe, Amlesh (Current Metabolomics and Systems Biology (Discontinued), 2020)
Introduction: Resveratrol and its monooxygenated metabolite oxyresveratrol were the subject matter of intense research due to their medicinal value. Absorption, distribution, metabolism and excretion are important to understand the bioavailability and pharmacokinetic profile of resveratrol and oxyresveratrol. Quantification of resveratrol and oxyresveratrol is essential for both in vitro and in vivo studies. Methods: During in vitro drug metabolism studies, both qualitative and quantitative information are essential to understand the metabolic profile of resveratrol and oxyresveratrol. In the present study, a simple and stable method is outlined using high performance liquid chromatography to quantify both resveratrol and oxyresveratrol. This method is suitable to understand the metabolic stability, plasma stability, pharmacokinetics and toxicokinetics of resveratrol and oxyresveratrol. Results: Generally, in vitro incubation studies are performed at high concentrations and in vivo studies are carried out at both high and low concentrations, therefore high performance liquid chromatography method is demonstrated as a suitable technique to quantify resveratrol and oxyresveratrol. Conclusion: Retention time of resveratrol and oxyresveratrol from liquid chromatography qualitatively confirm its identity.
Keywords: metabolism